2019
DOI: 10.1038/s41598-019-44747-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fine Radiographic Progression in Finger Joint Space Narrowing Beyond Human Eyes: Phantom Experiment and Clinical Study with Rheumatoid Arthritis Patients

Abstract: The visual assessment of joint space narrowing (JSN) on radiographs of rheumatoid arthritis (RA) patients such as the Genant-modified Sharp score (GSS) is widely accepted but limited by its subjectivity and insufficient sensitivity. We developed a software application which can assess JSN quantitatively using a temporal subtraction technique for radiographs, in which the chronological change in JSN between two radiographs was defined as the joint space difference index (JSDI). The aim of this study is to prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The second is that the resistance to apoptosis due to defects in tumor protein p53 triggers the hyperplastic synovium ( 53 , 134 ). Here, the shortage of chondrocytes caused by apoptosis would result in cartilage degeneration and joint-space narrowing via directed adhesion and invasion ( 53 , 135 , 136 ).…”
Section: Applications Of Msc Therapy In Ramentioning
confidence: 99%
“…The second is that the resistance to apoptosis due to defects in tumor protein p53 triggers the hyperplastic synovium ( 53 , 134 ). Here, the shortage of chondrocytes caused by apoptosis would result in cartilage degeneration and joint-space narrowing via directed adhesion and invasion ( 53 , 135 , 136 ).…”
Section: Applications Of Msc Therapy In Ramentioning
confidence: 99%
“…During the early stages of RA, JSN progression is usually less than 1 mm in 3 months [19]. Previous research could effectively detect changes only after waiting for a period of at least 1 or 2 years as human's minimum detectable change for joint space is about 0.4 mm [40]. In this phantom study, the measurement of 0.1 mm intervals had strong correlation and the SDC was as small as 0.02 mm on radiography postprocessed with POC.…”
Section: Discussionmentioning
confidence: 99%
“…A few clinical studies are available in the public domain (http://www .clinicaltrials.gov.) that evaluate the safety and efficacy of MSC-based therapy in RA, and some are still ongoing [10,[58][59][60][61]. So far, these proof-of-concept clinical translation studies have demonstrated promising results in terms of pathology resolution, safety, and efficacy with no to limited adverse events in patients with long histories of RA and particularly in refractory RA patients [59,61].…”
Section: Preclinical Animal Models Of Autoimmune Diseasesmentioning
confidence: 99%